Biological studies of novel aspirin-chalcone derivatives bearing variable substituents - Norsyafikah Asyilla, Nordin; Abdul Razak, Ibrahim; Zainab, Ngaini (2020)
The evolution of drug resistant bacteria has now becoming a major concern in the search for new antibacterial agent. Ongoing interest has also developing to find a new class of compounds with antioxidant properties. Herein, a series of hydroxylated chalcones 1a-g and aspirin-chalcone derivatives 2a-g were successfully synthesised for antibacterial and antioxidant properties. Chalcones 1a-g were prepared by Claisen-Schmidt condensation of 4-hydroxyacetophenone and benzaldehyde derivatives, while 2a-g were synthesised via esterification of aspirin with 1a-g. All the synthesised compounds were elucidated using CHNS elemental analysis, FTIR, 1H and 13C NMR spectroscopy, and X-ray crystallography. All compounds were evaluated for antibacterial assay via disc diffusion method and antioxidant assay using stable free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH). Only 1a showed moderate activity against Escherichia coli, while 1b-g and 2a-g showed no inhibition against E. coli and Staphylococcus aureus in comparison ampicillin as standard antibiotic. Compounds 1b-g and 2a-g having various substituents contributed to bulky molecular structures and caused difficult penetration into the cell membrane thus, unable to inhibit the bacterial growth. Compounds 1a-g and 2a-g also displayed poor antioxidant properties on DPPH in comparison to ascorbic acid due to low phenolic pharmacophore. The formation of bulky structures for 2a-g have hindered the antioxidant properties compared to 1a-g.